Thermal isolation system in an analytical instrument - WANG, TAK KUI; BAKER, JAMES WARD; BERGER, TERRY A (1998)
Sample analysis in a portable analytical instrument (100), preferably in the form of a gas chromatograph, benefits from temperature control of one or more thermal zones (108) in the instrument by way of a thermal isolation system (104) that includes a novel pumping assembly (124) to effect a selective amount of thermal isolation of the thermal zone. The pumping assembly includes a pumping element (210) in the form of a tubular or planar palladium structure (502). The pumping assembly (124) makes use of the unique properties of palladium to allow selective control of a nominal gas pressure within a vacuum cavity. A component system (106), which may include a separation column (318) and a thermal device (118) for heating and/or cooling the component system, may be provided within the vacuum cavity. The thermal device (118) and the pumping assembly are individually controlled by a control system (102). The pumping assembly (124) may be operated to allow selective control of the thermal isolation of the thermal zone; alternatively, the component system (106) may be subject to a controlled temperature by operating the thermal device. A sample mixture passing through the separation column (318) may thereby be exposed to a desired temperature profile according to a selected program so that the sample will separate into its components for subsequent detection by a detector (321).